The design of interactive coordination games - Reinhart Schmidt (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1980)
The design of Interactive coordination games has been described and discussed. The approach of a gaming system, which allows for a combination of gaming modules, is a necessary reply to the multiplicity of design factors. This approach enables the researcher to study human decision behavior and the efficiency of organizational Instruments under controllable conditions. The intro-duction of man-machine-interaction in the study of group behavior will lead to more efficient research on interaction between human beings.
Keywords: 650